Pengaruh Citra Merek Dan Harga Terhadap Keputusan Pembelian Produk Mustika Ratu Pada Pegawai Rumah Sakit Bunda Pengharapan - Simon Siamsa (Musamus Journal of Business & Management, 2019)
Research objectives To know the influence of brand image to buy product decisions Mustika Ratu in the employee hospital mothers Hope. Methods with a quantitative approach. Population and samples of 30 respondents using saturated sampling techniques and data analysis techniques: Simple regression assisted by SPSS. The results showed that the brand image of the t value is greater than t table that is 2.582> 1.703 and the value of sig, 016 because sig smaller 0.05 results show brand image has a positive and significant effect on purchasing decisions, while for the price variable t value greater than t table is 2.329> 1.703 and sig 0.028 smaller than 0.05 indicates that the price variables have a positive and significant effect on purchasing decisions. Keywords: brand image, price, purchasing decisions.